Introduction to occupational therapy - O'Brien, Jane Clifford; Hussey, Susan M. (St. Louis, Missouri : Elsevier, Mosby, 2013)
A complete overview of the profession and the practice of occupational therapy, 4th Edition prepares you for the roles, responsibilities, and relationships of the OT practitioner. This edition incorporates the latest revisions of the Occupational Therapy Practice Framework, which defines the OT process and areas of concern. Discussions also include treatment settings, occupational therapy across the lifespan, and evaluation, intervention, and outcomes within the OT process. Written by OT expert Jane Clifford O'Brien, this edition also keeps you current with emerging topics such as working with culturally diverse patients, evidence-based practice, and new practice areas such as driving and obesity. The latest revisions to the Occupational Therapy Practice Framework are incorporated throughout the book, keeping you current with today's OT theories and practice. New cultural content prepares you to meet the needs of diverse clients, and new discussions of the Centennial Vision provide a "big picture" view of occupational therapy and its changes as the profession reaches the age of 100
Introductory questions -- Looking back : a history of occupational therapy -- Philosophical principles and values in occupational therapy -- Current issues and emerging practice areas -- From student to practitioner : educational preparation and certification -- Professional organizations -- The occupational therapy practitioner : roles, responsibilities, and relationships -- Practicing legally and ethically -- Occupational therapy practice framework : domain and process -- Occupational therapy across the lifespan -- Treatment settings and models of health care -- Occupational therapy process : evaluation, intervention, and outcomes -- Service management functions -- Models of practice and frames of reference -- Intervention modalities -- Therapeutic relationships -- Clinical reasoning -- Appendix A. Occupational Therapy Code of Ethics and Ethics Standards (2010) -- Appendix B. Standards of practice for occupational therapy -- Appendix C. Key information from the occupational therapy practice framework
Includes bibliographical references and index.
Keywords: OCCUPATIONAL THERAPHY